Clinical value of Doppler echocardiography in the assessment of adults with aortic stenosis. Issue 6 (June 1985) - Simpson, I A; Houston, A B; Sheldon, C D; Hutton, I; Lawrie, T D
Abstract : Continuous wave Doppler echocardiography was used to study 41 adults with clinically suspected aortic stenosis undergoing cardiac catheterisation. Non-invasive assessment of the severity of stenosis was made before catheterisation using electrocardiograms, chest radiographs, and cross sectional echocardiography in addition to clinical examination and assessment modified, where appropriate, by the result of the Doppler examination. Catheterisation gradients were obtained in 33 patients and correlated well with those obtained by Doppler examination particularly when simultaneous recordings were obtained. All patients with surgically significant stenoses were identified by non-invasive assessment including Doppler examination and overestimation was not found in any patient with a less than significant stenosis. Thus surgery can be recommended in patients with aortic stenosis without the need for previous cardiac catheterisation.